APUCEN AN IDEAL PLATFORM TO CREATE A BETTER FUTURE FOR THE PEOPLE - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
PENANG, 25th April 2017 – The Asia-Pacific University-Community Engagement Network (APUCEN) which was officially launched in 2011, has now grown bigger with a total number of 90 members from 19 countries worldwide and with the aim of creating a better future for the people.